Polia (Polia) tiefi Pungeler 1914 - Varga, Zoltán; Ronkay, Gábor; Nagy, Jenő; Ronkay, László (Zenodo, 2020)
Polia (Polia) tiefi Püngeler, 1914 Polia (Mamestra) tiefi Püngeler, 1914, Deutsche Entomologische Zeitschrift, Gesellschaft Iris zu Dresden 28 : 38, pl. 2, fig. 22. Type-locality: [Russia] Sayan Mts, Munko-Sardyk. Lectotype: male, in coll. MNB. Taxonomic notes. This species was mentioned in the earlier publications as P. vesperugo (auct. nec Eversmann, HEYDEMANN 1944, HACKER et al. 2002) or P. schawerdae (Sheljuzhko, 1933). The synonymy with the latter species was established by VARGA et al. (2017). P. tiefi is widely distributed with some variation in the external appearance in the high mountains of NE Kazakhstan, South Siberia and Northern Mongolia (Saur, Tarbagatai, Sayan, Altai, Khangai and Khentij mountains), mostly in the upper mountain taiga zone. Published as part of Varga, Zoltán, Ronkay, Gábor, Nagy, Jenő & Ronkay, László, 2020, Contribution To The Taxonomy And Phylogeny Of The Genus Polia Ochsenheimer, 1816 (Noctuidae, Noctuinae, Hadenini): Species Groups And Pairs In The Holarctic Subgenus Polia S. Str., pp. 35-67 in Acta Zoologica Academiae Scientiarum Hungaricae 66 (1) on page 52, DOI:10.17109/AZH.66.1.35.2020, http://zenodo.org/record/5734753